The Maize ABA Receptors ZmPYL8, 9, and 12 Facilitate Plant Drought Resistance - He, Zhenghua; Zhong, Junwei; Sun, Xiaopeng; Wang, Bingcai; Terzaghi, William; Dai, Mingqiu (Frontiers in Plant Science, 2018)
Drought is one of the major abiotic stresses affecting world agriculture. Breeding drought-resistant crops is one of the most important challenges for plant biologists. PYR1/PYL/RCARs, which encode the ABA receptors, play pivotal roles in ABA signaling, but how these genes function in crop drought response remains largely unknown. Here we identified 13 PYL family members in maize (ZmPYL1-13). Changes in expression of these genes under different stresses indicated that ZmPYLs played important roles in responding to multiple abiotic stresses. Transgenic analyses of ZmPYL genes in Arabidopsis showed that overexpression of ZmPYL3, ZmPYL9, ZmPYL10 and ZmPYL13 significantly enhanced the sensitivity of transgenic plants to ABA. Additionally, transgenic lines overexpressing ZmPYL8, ZmPYL9 and ZmPYL12 were more resistant to drought. Accumulation of proline and enhanced expression of drought-related marker genes in transgenic lines further confirmed the positive roles of ZmPYL genes in plant drought resistance. Association analyses with a panel of 368 maize inbred lines identified natural variants in ZmPLY8 and ZmPYL12 that were significantly associated with maize drought resistance. Our results deepen the knowledge of the function of maize PYL genes in responses to abiotic stresses, and the natural variants identified in ZmPYL genes may serve as potential molecular markers for breeding drought-resistant maize cultivars.